Imperial confederations and nomadic associations of Central Asia (historiography of problem) - Maydanali, Z (Journal of history, 2020)
Main conceptual positions and methodological paradigms to problem «leading a nomadic life empire» are considered in the article. There are considered different approaches and methods of the study of the shaping and operating the political system «leading a nomadic life empire». The onward development to modern history thought in study social-political sphere of the nomadic formation is shown. Analysis of the modern historiography on the continuity and transformation of the political organization of nomadic societies in research surveys and discourse observed processes of different directions. Research evidence shows that it is necessary to take into account the problem of succession, analogies and special features of the state in the imperial tradition of the Imperial confederations. The article deals with diversified approaches to the problems by adding the migratory habits of political entities of their systematization and reconstruction of a complex set of different types and models of power coupled into a single imperial structure.